Symmetries of Touch: Reconsidering Tactility in the Age of Ubiquitous Computing. (March 2022) - Ladewig, Rebekka; Schmidgen, Henning
Engaging with the specific ways current media technologies interact with, or directly access the human body, we suggest developing a 'symmetrical' theory of touch. Critically referring to Bruno Latour's invocation of 'symmetrical anthropology', we reconsider tactile agency as 'technological agency', arguing that the concept of touch – traditionally viewed as an exclusively human ability – should be extended to non-human actors and analysed in view of the cultural logic of capitalism. Its systematic focus, then, is on the productive intersections and contact zones between biology and technology: from phenomena of non-human touch in industrial production (lathing, printing, etc.) to the material touching taking place in the instrumental grasp on the living in the 19th-century physiological laboratories and the invisible operations of tracing, tracking and sensing taking place in the technological milieus of today's (media) environments. In highlighting the tactile dimension of digital modernity and its economic genealogies, this article aims to advance a combined concept of human and non-human touch which provides a crucial angle for reconsidering bodies and technologies in the age of ubiquitous computing.